The Influence of Social Presence on Purchase Intention in Live Video Commerce (Empirical Study in Bandung City) - Putri, Anida Juliana; Syahputra, Syahputra; Pradana, Mahir (Journal of Applied Business, Taxation and Economics Research, 2024)
The rapid development of internet technology has changed the way we live and interact. The increasing number of internet users in Indonesia has encouraged business actors to be more innovative in marketing their products digitally. The emergence of direct shopping features on various social media platforms has revolutionized the way consumers shop, allowing transactions to occur instantly and interactively. There is competition between e-commerce that uses live video features such as Shopee, TikTok, Tokopedia, and Lazada. This study aims to determine the role of social presence on purchase intention mediated by immersive experience and trust in live video commerce features in Indonesia. The research methodology employed is a descriptive and quantitative approach, which utilizes data acquisition techniques through online questionnaires to obtain 385 respondents. Purposive sampling is implemented in conjunction with nonprobability sampling. The data collected will be analyzed using SmartPLS version 3.9. The results of this study found that social presence has no effect on purchase intention. Keywords: Social Presence, Live Video Commerce, Purchase Intention.